Distribution of socioeconomic factors among the new patients of skin cancer in Iran - Jafari, Mehdi; Heydari, Parvane; Mahmoudian, Payam; Nemati, Ali; Mohammad-Pour, Saeed; Hosseini, Seyede-Elahe (Social Determinants of Health, 2017)
Background: The global burden of cancer due to population growth and aging, and various environmental factors is increasing. Skin cancer is the most common cancer among Iranians and among men, is more common. There is strong evidence from Industrialized and less developed countries that cancer incidence and survival is related to socioeconomic factors. The aim of this study was to investigate the relationship between socioeconomic variables including Human Development Index, unemployment rate and Urbanization ratio with the incidence of skin cancer in Iran. Method: The panel data were for 30 provinces for 6 years) 2007 to 2012(. Data of socioeconomic factors were collected from the Statistical Center of Iran and the data related to the incidence of cancer were collected from the reports on cancer registry of Health and Medical Education Ministry. For data analysis Stata11th version was used. Result: There is no relation between unemployment and the incidence of skin cancer. There is negative relationship between urbanization and incidence of skin cancer in both sexes. There is negative relation between HDI and the incidence of skin cancer in both sexes. Conclusion: Among the three variables selected in this study, the human development index and the urbanization, influenced on the cancer incidence. Therefore, in order to prevent skin cancer, paying attention appears to be necessary for policymakers. Key words: Socioeconomic Factors, Skin Neoplasm, Iran